The Influence Of Booklet And Tiktok Video Media Counseling Towards Students' Knowledge And Attitudes About Early Marriage At Sman 1 Sei Rampah - Siti Nurjannah; Mindo Siagian; Frida Lina Tarigan; Donal Nababan; Seri Asnawati (Jurnal Info Sains : Informatika dan Sains, 2023)
Early marriage or marriages that occur among underage children became one of the phenomenon in community environment. Its is because this is something that has been happening for a long time and it is nothing new anymore. According to BPS in Sei Rampah Sub-Distric,t the percentage of early marriages in 2021 up to 2022 among women aged 10-16 years was 5.93%, indicating that the rate of early marriages is still high in Sei Rampah Sub-District. This research aim to determine the influence of Booklets Media and TikTok Videos Counseling on The Students’ Knowledge and attitude concerning Early Marriage at SMAN 1 Sei Rampah. This research uses an experimental method with a pre-experimental design using two sample groups as the comparison. The number of population was 161 people. The number of samples was 120 people. Data were collected by filling out the pretest questionnaire, namely before respondents received counseling treatment and posttest after respondents received counseling treatment to determine the students’ knowledge and attitudes. The sampling technique uses probability sampling technique with simple random sampling technique. Data were analyzed using the Wilcoxon test. the results of this research test show that the level of knowledge before and after being given counseling using booklet media has the difference in mean value of 0.400 and a significance of 0.00, p-value <0.05 so there is a significance difference. In the attitudes before and after being given counseling using booklet media there was a difference in mean value of 0.333 and a significance of 0.157, p-value <0.05, so there was no significant difference. At the level of knowledge before and after being given counseling using TikTok video media, there is a mean difference of 0.400 and a significance of 0.00, p-value <0.05, so there is a significant difference. In the attitudes before and after being given counseling using TikTok video media, there was a mean difference of 0.133 and a significance of 0.01, p-value <0,05, so there was a significant difference. Thus, it is recommended for schools authorities to provide the facilities and infrastructures such as provided the learning media booklets and Tiktok videos, and also can collaborate with various agencies such as the Health Service, BKKBN to jointly prevent early marriage among teenagers.